Promoting improved rainwater and land management in the Blue Nile (Abay) basin of Ethiopia - Merrey, Douglas J.; Gebreselassie, T. (International Livestock Research Institute, 2011)
This paper is an attempt to draw together and synthesise as much of the existing documentation as is possible within a limited time period, analyse it systematically, and draw out the main conclusions, lessons learned, and gaps in knowledge. The report tries to identify which RWM innovations have worked when, where and why; what did not work out very well, and why; and what lessons can be extracted from past experience to guide CPWF research in the Nile over the next 4–5 years. It takes a broad approach, addressing policy and institutional issues at multiple levels, experiences and lessons from major implementation and research programs, the outcomes and impacts of specific RWM interventions, experiences with targeting, and other topics. The paper also makes recommendations intended to provide support to the planning and implementation of CPWF Projects N2–N5 as well as other research for development programs. In short, the report contains the findings and recommendations of the study, including, as stated in the terms of reference: Summaries of the findings of past and on-going studies on RWM strategies, including impacts on water productivity, success as well as failure in improving agricultural production and livelihoods— and the reasons for these, negative as well as positive social and environmental impacts (e.g. upstream–downstream consequences, increasing transmission of vector borne disease), analysis of factors influencing RWM adoption or disadoption behaviour, including an analysis of policy or institutional factors at different levels (local, regional, federal) that may directly or indirectly influence the use of improved RWM strategies. An inventory of institutions and individuals working in the past and in the present on RWM—and which of these might be suitable CPWF BDC partners.